Individuals with psychosis receive less electric field strength during transcranial direct current stimulation compared to healthy controls - Rebecca Kazinka; Da Som Choi; Alexander Opitz; Kelvin O. Lim (Schizophrenia)
Abstract Recent research has examined the effectiveness of transcranial direct current stimulation (tDCS) as an adjunctive treatment for antipsychotics, finding mixed results on cognitive, positive, and negative symptoms. We tested if individuals with psychosis have reduced electric field strength compared to healthy controls and assessed the potential causal factors. We hypothesized that either cortical thinning due to the disorder or increased scalp thickness due to secondary effects of the disorder were causal factors. Using the Psychosis Human Connectome Project dataset, we simulated electric field models for 136 individuals with psychosis, 73 first-degree relatives, and 43 healthy controls. We compared group differences of electric field strength at bilateral dorsolateral prefrontal cortex (dlPFC), targeted with two montages (Fp1-Fp2 & F3-Fp2) commonly used to treat cognitive impairment. We additionally compared groups on scalp, skull, and cerebrospinal fluid thickness at bilateral dlPFC and the three electrode locations. Mediation analyses assessed if tissue thickness and BMI were causal factors for group differences while controlling for age and sex. Individuals with psychosis had lower electric field strength for bilateral dlPFC for both montages. Scalp thickness was also greater for individuals with psychosis, but cerebrospinal fluid thickness was not significantly different. BMI was a significant mediator for the group difference seen in both scalp thickness and electric field strength. Future treatment studies using tDCS in the psychosis population should include electric field modeling to assess its effectiveness given the increased risk of obesity. Individualized montages based on head models may also improve effectiveness.